2007
DOI: 10.1038/nm1671
|View full text |Cite|
|
Sign up to set email alerts
|

Pim-1 regulates cardiomyocyte survival downstream of Akt

Abstract: The serine-threonine kinases Pim-1 and Akt regulate cellular proliferation and survival. Although Akt is known to be a crucial signaling protein in the myocardium, the role of Pim-1 has been overlooked. Pim-1 expression in the myocardium of mice decreased during postnatal development, re-emerged after acute pathological injury in mice and was increased in failing hearts of both mice and humans. Cardioprotective stimuli associated with Akt activation induced Pim-1 expression, but compensatory increases in Akt a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
311
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 224 publications
(335 citation statements)
references
References 48 publications
12
311
2
Order By: Relevance
“…For example, a recent study suggested that Pim and AKT work in concert to regulate survival and proliferation of nontransformed hematopoietic cells (Hammerman et al, 2005). More recently, another group described a novel discovery that Pim-1 is a crucial facet of cardioprotection downstream of AKT and that a feedback mechanism exists involving the two proteins (Muraski et al, 2007). Importantly, Pim kinases show similar substrate specificity as AKT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, a recent study suggested that Pim and AKT work in concert to regulate survival and proliferation of nontransformed hematopoietic cells (Hammerman et al, 2005). More recently, another group described a novel discovery that Pim-1 is a crucial facet of cardioprotection downstream of AKT and that a feedback mechanism exists involving the two proteins (Muraski et al, 2007). Importantly, Pim kinases show similar substrate specificity as AKT.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that AKT and Pim-1 show feedback relationship in some cell types (Muraski et al, 2007). It has also been found that AKT shows similar substrate specificity as Pim kinases.…”
Section: Akt1(e17k) Promotes Survival Of Pim-deficient Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The serine/threonine kinase Pim-1 is a critical downstream effector of Akt-mediated cardioprotective signaling (15)(16)(17)(18). Pim-1 is antiapoptotic and proproliferative, and recent findings indicate that it also exerts beneficial effects in part by preserving mitochondrial integrity (15).…”
mentioning
confidence: 99%